Rasch-Based Diagnostic Analysis of Biology Education Students’ Conceptual Difficulties In Work and Energy - I Made Hermanto; Wahyu Mu'zizat Mohamad; Lukman Samatowa; Ganesha Antarnusa (Islamic Journal of Integrated Science Education (IJISE), 2026)
This study aimed to analyze Biology education students’ conceptual difficulties in work and energy using the Rasch Model. A descriptive quantitative approach with a diagnostic survey design was employed. The participants were 21 Biology education students who had learned the topic of work and energy. The instrument consisted of 15 diagnostic multiple-choice items scored dichotomously, with 1 indicating a correct answer and 0 indicating an incorrect answer. The data were analyzed using the Rasch Model to examine instrument quality, item fit, item difficulty, Wright Map, score-category monotonicity, and students’ conceptual difficulty patterns. The results showed that students’ average ability was higher than the average item difficulty, with a mean person measure of 1.61 logits. However, the person reliability of 0.08 and person separation index of 0.30 indicated that the instrument had limited ability to distinguish students across different ability levels. The most difficult items were Q14, Q3, Q11, Q13, and Q15, which were related to the application of work, potential energy, and mechanical energy conservation. In contrast, Q2, Q4, Q5, and Q9 were the easiest items because they mainly assessed basic conceptual recognition. These findings indicate that students’ main difficulties were not in recognizing basic terms but in applying and integrating work and energy concepts in physics contexts.